2020
DOI: 10.1039/d0sc01678k
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic solder for assembling bulk covalent adaptable network blocks

Abstract: Covalent adaptable networks (CANs) can be reprocessed and recycled relying on reversible covalent bond structures. Magnetic solders enable flexibly welding of bulk CAN blocks by the magnetothermal effect induced bond exchange reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 55 publications
(55 reference statements)
1
31
0
Order By: Relevance
“…Notably, as we investigated previously, bulk CAN materials cannot be welded together by direct heat because the heating will act on all the samples, leading to the overwhelming shape destruction under pressure. Light is also very difficult to work on welding bulks, as the overlapped regions are covered by the thick “body” of the bulk material, making light blocked ( 40 ). By AMF-assisted welding, we fabricated monolithic magneto-responsive multimaterial actuators with heterogeneous structures (experimental details can be found in Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, as we investigated previously, bulk CAN materials cannot be welded together by direct heat because the heating will act on all the samples, leading to the overwhelming shape destruction under pressure. Light is also very difficult to work on welding bulks, as the overlapped regions are covered by the thick “body” of the bulk material, making light blocked ( 40 ). By AMF-assisted welding, we fabricated monolithic magneto-responsive multimaterial actuators with heterogeneous structures (experimental details can be found in Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Fe 3 O 4 NPs exhibit high magnetothermal conversion rates under the action of AMF and are commercially available (41,42). It was found that Fe 3 O 4 NPs were well distributed in common PU systems in our previous work (40). To obtain M-PULCEs with favorable large-scale shape deformations, we prepared liquid crystal (LC) oligomers to decrease the cross-link density and prolong the chain length of the LC moieties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds were identified as 3′-chlorotrypacidin ( 166 ), asterric acid ( 167 ), methylasterrate ( 168 ), methyl-4′,6′-dichloroasterrate ( 169 ), and methyl-4′-chloroasterrate ( 170 ). The inhibition rates of compounds 165 and 166 (at 500 μM) against Curvularia lunata were 100% and 67.6%, respectively, and they showed strong inhibitory activity against Bacillus subtilis [ 47 ]. An endophytic fungus isolated from the phloem of C. anglatus was identified as Fusarium proliferatum and three cyclopeptides isolated from this strain were named enniatin A1 ( 171 ), enniatin B1 ( 172 ) and enniatin B ( 173 ) [ 48 ] (Fig.…”
Section: Celastrus Anglatus Maximmentioning
confidence: 99%